An Exploratory Study On Knowledge Transfer At A University Conference - Rollof, Jan; Sefcik, Michael (Journal of Knowledge Management Practice, 2010)
The main hypothesis behind this exploratory study was that lecture settings and formats may influence the efficiency of knowledge transfer in the context of conferences. To address this topic, questionnaires were sent to participants of a scientific conference before, a few days after, and again approximately 3 months after a conference. The results suggest that interactive formats may be more efficient than one-way communication. Further, this study indicates that the methodology of using pre-, post-, and follow-up questionnaires may be well suited for the evaluation of knowledge transfer in this context. Such information may also be valuable for conference organizers.